2012
DOI: 10.1007/s11302-012-9311-x
|View full text |Cite
|
Sign up to set email alerts
|

New insights regarding the regulation of chemotaxis by nucleotides, adenosine, and their receptors

Abstract: The directional movement of cells can be regulated by ATP, certain other nucleotides (e.g., ADP, UTP), and adenosine. Such regulation occurs for cells that are "professional phagocytes" (e.g., neutrophils, macrophages, certain lymphocytes, and microglia) and that undergo directional migration and subsequent phagocytosis. Numerous other cell types (e.g., fibroblasts, endothelial cells, neurons, and keratinocytes) also change motility and migration in response to ATP, other nucleotides, and adenosine. In this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 145 publications
(90 reference statements)
3
70
0
Order By: Relevance
“…Neurons and SCs in the PNS express purinergic receptors that are linked to the release of intracellular Ca 2+ stores and the regulation of several pathways [27][28][29][30]. Moreover, the actions of extracellular UTP nucleotide in SCs remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons and SCs in the PNS express purinergic receptors that are linked to the release of intracellular Ca 2+ stores and the regulation of several pathways [27][28][29][30]. Moreover, the actions of extracellular UTP nucleotide in SCs remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…While several reports have shown that nucleotides can induce the migration of different cell types in culture [27], cell migration is a complex coordinated process of cell polarization, protrusion of the cytoplasm, adhesion, and forward displacement of the cell [38]. In the present study, live imaging experiments revealed that in cultures that were treated with apyrase, glial cells at the border of the scratch formed only small cytoplasmic protrusions that soon retracted toward the cell soma.…”
Section: Discussionmentioning
confidence: 38%
“…Since nucleotides induce the expression of N-cadherin in cultured astrocytes [42] as well as in transformed cells [43], one Cell migration entails activation of a variety of molecular and cellular events that converge in morphological changes and cell displacement. Different intracellular signaling pathways activated by membrane receptors were implicated in these events, including nucleotide receptors [27]. For example, phosphorylation of Akt and FAK induced by nucleotides and EGF were associated with migration of neural stem cells [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Released by damaged or stressed cells, extracellular ATP acts as a danger signal and induces inflammasome activation, as well as the release of inflammatory cytokines, being strong pro-inflammatory stimuli. Extracellular ATP also promotes phagocyte chemotaxis and leads to damaged cell clearance, as beautifully revised by Corriden and Insel [8]. Accumulated extracellular ATP gradually suffers enzymatic hydrolysis into adenosine, which, in turn, is read as a Breporter of excessive tissue damage,^as shown by Bono et al [9] As such, adenosine signaling is interpreted as an anti-inflammatory stimulus, generally opposing the effects induced by ATP.…”
Section: Extracellular Adenosine Production and Adenosine Signalingmentioning
confidence: 97%